Improvement Proposal to Reduce Defects in PET Bottle Blowing Using Lean Six Sigma: Case Study - Leon Castro, Rocio; Huancas Mitma, Carlos; Barahona Rodriguez, Sebastian; Barahona Rodriguez, Diego; Quispe Vara, Lucía; Morocho Pérez, Maria (LACCEI, 2025)
This study has a pre-experimental design, in which the application of the Lean Six Sigma methodology is proposed for the production process of 2.5L PET bottles in a mineral water and ice company. Through the DMAIC approach, it was identified that the most frequent defects arise in the preform blowing process, representing 55% of the total defects. Various tools were used to analyze the information, such as the SIPOC diagram to map the overall process, the VSM to visualize the production process and potential improvements, the Pareto diagram to identify the priority aspects to address, and the Ishikawa diagram and 5 Whys to analyze the root cause. It was determined that the lack of temperature and humidity control in preform storage is the main cause. As a proposal, it is recommended to install an environmental control system with dehumidifiers and climate control, as well as the implementation of an intelligent temperature control system to improve process efficiency. These actions are estimated to reduce blowing defects by 50%, significantly improving the sigma level from 4.13 to 4.35, and increasing the yield from 99.57% to 99.79%. Additionally, the use of Poka-Yoke sensors is suggested to maintain quality control throughout the process